HUBUNGAN FAKTOR LINGKUNGAN FISIK DAN PERILAKU KELUARGA TERHADAP KEJADIAN DEMAM BERDARAH DENGUE (DBD) - Azza, Awatiful; Nurdin, Nurdin; Zamli, Zamli; Marni, Marni; Mudhofar, Muhamad Nor (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Dengue fever (DHF) is a public health problem because the number of cases and spread tends to increase, and often causes Extraordinary Events (KLB). The disease is transmitted by the Aedes aegypti mosquito with four main clinical manifestations characterized by circulatory failure. The purpose of this study was to determine the relationship between Physical Environmental Factors and Family Behavior towards the Incidence of Dengue Fever in the Sebanga Health Center Working Area. The research method used a cross sectional research design. The population in this study were people who lived in the Sebanga Health Center working area with a sample of 62 people. The data collection technique used total sampling. The research instrument used a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed that there was a relationship between environmental factors (p value: 0.000) and family behavior (p value: 0.000) with the incidence of DHF. It is recommended for health workers to be able to provide education to the community about health behavior in order to increase mosquito eradication movements by cleaning the surrounding environment, always routinely once a week cleaning water reservoirs, recommending to install, wire gauze ventilation, suggesting that a room area > 8 m² is used for 2 or more people, and planting ornamental plants to maintain room humidity to the community.Keywords: DHF, environment, family